2017
DOI: 10.4103/0972-0707.219203
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric analysis of coronal discoloration induced by white mineral trioxide aggregate and Biodentine: An in vitro study

Abstract: Aims:The aim of this study was to evaluate the specific chromatic alterations in tooth crowns induced by two different endodontic restorative materials.Settings and Design:This in vitro study was conducted at the Department of Conservative Dentistry, KMCT Dental College, Kozhikode, Kerala.Subjects and Methods:Forty-five freshly extracted, fully developed, single-rooted teeth were prepared and randomly assigned to two experimental groups (n = 15 each) and one negative control group (n = 15). Group 1 consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
3
6
0
2
Order By: Relevance
“…This result was in agreement with the results of Asgary et al, Ioannidis et al, Aldakak et al, and Bhavya et al who reported that Biodentine did not change colour of the tooth and results of Shokouhinejad et al, Yoldaş et al, and Kahler et al who reported that Biodentine exhibited significantly less discoloration when compared to MTA.…”
Section: Discussionsupporting
confidence: 92%
“…This result was in agreement with the results of Asgary et al, Ioannidis et al, Aldakak et al, and Bhavya et al who reported that Biodentine did not change colour of the tooth and results of Shokouhinejad et al, Yoldaş et al, and Kahler et al who reported that Biodentine exhibited significantly less discoloration when compared to MTA.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained from present study exhibit that CHX and NaOCl cause considerable discoloration. These results are in congruence with previously reported studies (26,27).…”
Section: Discussionsupporting
confidence: 94%
“…When comparing formocresol to ferric sulfate, a recent systematic review indicates that the total success rate at 2 years for formocresol was 87.1% and ferric sulfate was 84.8%, with the meta–analysis favoring neither agent’s success [30]. Biodentine TM was investigated in the current study because it was recently marketed and showed success in several clinical applications such as endodontic and restorative dentistry [810]. Because of its regenerative properties, it was suggested to be used as a suitable replacement to formocresol in pulpotomy of primary teeth [31].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Septodont developed a new tricalcium–silicate cement (Biodentine TM ) which could join perfect mechanical features with outstanding biocompatibility, in addition to a bioactive performance [7]. Biodentine TM has been introduced and progressed (through active biosilicate technology) with the purpose of incorporating the increased biocompatibility and bioactivity of calcium silicates, producing improved features that cause it to be better than any other calcium silicate–based cements such as quick setting time, high compressive strength, and easy dealing with as well as its many uses in both endodontics and restorative dentistry without resulting in discoloration of the treated teeth [810]. Biodentine TM drew awareness in the specialty of endodontics due to its excellent sealing ability, handling properties, biocompatibility, stability, long–term impermeability, low solubility, quick setting time, and capability to induce hard tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation